Determinación del impacto de competencia de diferentes cohortes de avena silvestre (Avena fatua) sobre los rendimientos en un cultivo comercial de trigo (Triticum aestivum) - Márquez M., Javier; Salas A., Jacobo; Fuentes D., Cilia L.; Plaza T., Guido A. (Agronomía Colombiana, 1996)
The objective of this study was to determine the behaviour of wild oats (Avena fatua L.) in a wheat crop (Tritícum aestivum LO.). This research was conducted at the Centro Agropecuario "Marengo" , Universidad Nacional de Colombia, near the town of Mosquera, Cundinamarca. In order to determine the variation of Avena fatua populations, 8 succesive cohorts were established with intervals of 15 days. The experimental design used was randomized complete blocks with tour replications. In addition to the the eight treatments (cohorts) there were two check plots, one was kept always clean and the other was kept always weedy. Each cohort was examined for phenological changes twice per week, and the impact of competition was established on the basis of dry weight of each plant. Differences were observed among the oat cohorts. In the tirst five cohorts, oat plants were as tall as wheat plants, and density and dry weight were higher than for the last three cohorts. Plants from cohorts 6 th 7th and 8th had less number of stems and lower dry weight. These differences among cohorts suggest a stronger competitive impact on crop yield from the earlier oats populations.